2015
DOI: 10.1002/cncr.29615
|View full text |Cite
|
Sign up to set email alerts
|

Inherited mutations in cancer susceptibility genes are common among survivors of breast cancer who develop therapy‐related leukemia

Abstract: Background Risk factors for therapy-related leukemia (TRL) development, an often lethal late complication of cytotoxic therapy, remain poorly understood and may differ for survivors of different malignancies. Breast cancer (BC) survivors now account for the majority of TRL cases, making study of TRL risk factors in this population a priority. Methods Patients with TRL following cytotoxic therapy for a primary BC were identified from The University of Chicago TRL registry. Those with an available germline DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 146 publications
(107 citation statements)
references
References 32 publications
4
103
0
Order By: Relevance
“…§Mutations in genes associated with cancer predisposition genes such as TP53 and BRCA1/2 appear to be frequent in therapy-related myeloid neoplasms. 256 …”
Section: Fanconi Anemiamentioning
confidence: 99%
“…§Mutations in genes associated with cancer predisposition genes such as TP53 and BRCA1/2 appear to be frequent in therapy-related myeloid neoplasms. 256 …”
Section: Fanconi Anemiamentioning
confidence: 99%
“…25 Consistent with these data, a study of breast cancer survivors with therapy-related leukemia identified germ line mutations in BRCA1, BRCA2, TP53, CHEK2, and PALB2 that collectively accounted for 21% of cases. 26 Interestingly, in this second study, there were 7 patients with therapy-associated ALL, with 2 (50%) of 4 tested harboring germ line TP53 mutations. 26 Together, the data from these studies suggest that individuals with therapy-associated leukemia should be considered as candidates for a possible genetic evaluation.…”
Section: Presenting Features Of the Tumor And Histologymentioning
confidence: 74%
“…26 Interestingly, in this second study, there were 7 patients with therapy-associated ALL, with 2 (50%) of 4 tested harboring germ line TP53 mutations. 26 Together, the data from these studies suggest that individuals with therapy-associated leukemia should be considered as candidates for a possible genetic evaluation.…”
Section: Presenting Features Of the Tumor And Histologymentioning
confidence: 74%
“…74,75 Thus, the history of previous cytotoxic therapy in a patient with t-AML or therapy-related lymphoblastic leukemia is important for diagnosis and classification but also, perhaps, for identification of an inherited predisposition to drug-induced cancer. 76 As noted in the preceding section, a history of radiation therapy-either alone or in combination with chemotherapy for prior neoplastic or nonneoplastic conditions-is recognized as being associated with an increased risk for AL, particularly AML. Radiation exposure for individuals near natural disasters or atomic bomb explosions is also associated with an increased risk of leukemia, 77,78 and reportedly, radiation exposure after diagnostic procedures, including computed tomography scans in children, increases the risk for leukemia.…”
Section: Strong Recommendationmentioning
confidence: 97%